Pengaruh Brand Image, Perceived Quality, Perceived Price terhadap Niat Beli Survei Pada Generasi Muda Calon Konsumen Produk Thrift di Daerah Istimewa Yogyakarta - Akbarudin Fikri Anwar; Surpiko Hapsoro Darpito; Hasa Nurrohim (Jurnal Ilmiah Manajemen Kesatuan, 2022)
This study aims to analyze the effect of Brand Image, Perceived Quality, and Perceived Price on Purchase Intention (Survey of the Young Generation of Thrift Product Consumers in the Special Region of Yogyakarta). The design of this research is descriptive and quantitative research using purposive sampling method, namely research conducted by sampling technique with certain considerations. Data collection was carried out in June 2022. The study population was all people who live in the Special Region of Yogyakarta. The samples studied were 120 respondents. Primary data collection technique is done by distributing questionnaires using google form. This study uses the Statistical Package for the Social Sciences (SPSS) 25.0 for Windows analysis tool. The results of this study indicate that 1) Brand Image, Perceived Quality, and Perceived Price have a positive and significant effect on Purchase Intention, 2) Brand Image has a positive and significant effect on Purchase Intention, 3) Perceived Quality has a positive and significant effect on Purchase Intention, 4) Perceived Price has a positive and significant effect on Purchase Intention. The R2 value of 0.513 means that 51.3% of the variation of Purchase Intention on thrift products can be explained by the Brand Image, Perceived Quality and Perceived Price variables, the remaining 48.7 is explained by other variables outside of this study.